Idiopathic membranous nephropathy with renal amyloidosis: A case report - Wang, Yue; Wang, Xueyao; Yu, Jinyu; Wu, Shan; Xu, Zhonggao; Sun, Weixia (Frontiers in Medicine, 2022)
Background: Immunoglobulin light chain amyloidosis is a clonal, nonproliferative plasma cell disorder, in which fragments of immunoglobulin light chain are deposited in tissues. Clinical features depend on organs involved but can include restrictive cardiomyopathy, nephrotic syndrome, hepatic failure, peripheral/autonomic neuropathy, and atypical multiple myeloma. Membranous nephropathy (MN) is a group of diseases characterized by deposition of immune complexes under the epithelial cells of glomerular basement and diffuse thickening of the basement membrane. Most patients with idiopathic MN (IMN) have been exposed to phospholipase A2 receptor (PLA2R) antigen, and anti-PLA2R antibodies that attack podocytes can be detected in their blood. IMN combined with amyloidosis nephropathy without secondary factors is rare. The present study describes a patient with IMN combined with immunoglobulin light chain amyloidosis nephropathy. Case Report: A 39-year-old man was admitted to our hospital because of weight loss and edema. His clinical manifestation was nephrotic syndrome. Renal pathology revealed MN. A positive Congo red staining and the pathognomonic apple-green birefringence under cross-polarized light were considered to be associated with amyloid nephropathy. Immunofluorescence showed that λ light chain was positive. Heavy chain deposition disease and amyloid-associated protein amyloidosis were excluded by immunofluorescence and immunohistochemistry, respectively. Subsequent examinations showed that his serum was negative for antibodies against the PLA2R, but PLA2R was present in renal tissue. The final diagnosis was IMN with light chain amyloid nephropathy. Conclusions: Renal amyloidosis accompanied by IMN is uncommon. Attention should be paid to the subtype of the disease and the exclusion of secondary factors. Perfect clinical and pathological examination are helpful for the classification and staging of the disease. Congo red staining, light microscopy, immunofluorescence, immunohistochemistry, electron microscopic examination, pathological tissue staining for PLA2R antigen and testing for anti-PLA2R antibody in serum are helpful.